Drug‐Sponge Lipid Nanocarrier for in Situ Cargo Loading and Release Using Dynamic Covalent Chemistry. (4th February 2021) - Liu, Fei; Niko, Yosuke; Bouchaala, Redouane; Mercier, Luc; Lefebvre, Olivier; Andreiuk, Bohdan; Vandamme, Thierry; Goetz, Jacky G.; Anton, Nicolas; Klymchenko, Andrey
Abstract: Currently, drug‐delivery strategies using nanocarriers (NCs) deal with encapsulation of cargo or its covalently modified prodrug. Herein, we propose a concept of reversible pH‐controlled capture and delivery of active cargo based on dynamic covalent chemistry inside lipid nano‐droplets (nanoemulsions), coined as "drug sponge". We designed a highly lipophilic hydrazide (LipoHD) capable of reacting with a free cargo‐ketone (fluorescent dye and doxorubicin drug) directly inside lipid NCs, yielding a lipophilic hydrazone prodrug efficiently captured in the oil core. LipoHD‐loaded NCs spontaneously accumulated cargo‐ketones, yielding formulations stable against cargo leakage at pH 7.4, and further released their dye/drug cargo at low pH range (5.0–6.8) in solution and live cells. Doxorubicin‐loaded drug‐sponge NCs showed cytotoxicity in four cancer cell lines and capacity to inhibit tumor growth in subcutaneous xenografts of mice. Finally, unprecedented extraction of dye/drug cargos directly from cells and tissues (i.e. detoxification) was realized by the drug‐sponge NCs. Abstract : A drug‐sponge nanocarrier that reversibly captures and releases drugs or contrast agents under pH control is developed using dynamic covalent chemistry. Inside this lipid droplet nano‐reactor, lipophilic capture molecules transform free cargo‐ketones into encapsulated hydrazone prodrugs, enabling the controlled release of active cargos and also their extraction from cells and tissues for detoxification.